Remote Working Management Skills for HR Professionals: Handbook for Trainers - Ferjan , Marko; Mazurek, Artur; Mitrut, Katarzyna; Vourda, Aglaia; Solomos, Dioniysios; Ferreira, Aristides I.; Bernik, Mojca (University of Maribor Press, 2022)
The handbook “Remote working management skills for HR professionals-HANDBOOK FOR TRAINERS” is related to online training for HR professionals. In the handbook, we present the curricular aspects of the training. The emphasis is on the following: list of skills for mangers; list of learning outcomes; list of learning contents; learning strategies and methods; learning materials; instructions for examination and grading; instructions for implementation. There are six learning modules in the list of learning contents: Communicational skills, Digital skills, Work-life balance, skills, Organizational skills, Leadership skills and HRM skills. For each learning module, we prepared the learning material: Case studies; Practical exercises; Questions and answeres; Multiple choice questions. The trainer also has available for each learning module: Power point presentations (5 files for each learning module); Lecture notes (10-15 pages for each learning module). Presentations and lecture notes are not included in this handbook. They are published separately.